Effects of Different Levels of drought Stress on Yield and Yield Components of Quinoa (Chenopodium Quinoa Willd.) - Hossein Beyrami; Rostam Yazdani- Biouki; Masoumeh Salehi (آب و توسعه پایدار, 2024)
Due to the limited quality of water resources and considering that the majority of the country is arid and semi-arid, it is important to cultivate plants with a high tolerance to drought and salinity. This research was conducted to determine the effect of different moisture levels on yield and yield components of quinoa (Chenopodium quinoa Willd.) under lysimetric conditions in the spring and autumn cropping seasons. Treatments included irrigation after draining 0.2, 0.4, 0.6, and 0.8 of the total available water (TAW). Irrigation was done based on the soil moisture depletion and the leaching requirement of about 20%. At the end, dry biomass, seed yield, and yield components were measured. The results showed that with an increase in the moisture depletion from 0.6 to 0.8 TAW, the biomass and seed yield had a significant decrease of 24 and 37% in the spring and 34 and 47% in the autumn cropping season, respectively. But the increase in moisture depletion from 0.2 to 0.4 and 0.4 to 0.6 did not cause a significant decrease in these traits. The results indicated that changes in moisture depletion levels caused significant differences in plant height (P<0.01), stem diameter, and 1000-seed weight (P<0.05) in spring cropping, but their effect on panicle length and width and the number of secondary stems was not significant. In the autumn cropping season, the results showed that changes in moisture levels caused significant differences in plant height and the 1000-seed weight (P<0.01), but the effect on other yield components was not significant.